2021
DOI: 10.3390/ijms22031013
|View full text |Cite
|
Sign up to set email alerts
|

Cargo Recognition and Function of Selective Autophagy Receptors in Plants

Abstract: Autophagy is a major quality control system for degradation of unwanted or damaged cytoplasmic components to promote cellular homeostasis. Although non-selective bulk degradation of cytoplasm by autophagy plays a role during cellular response to nutrient deprivation, the broad roles of autophagy are primarily mediated by selective clearance of specifically targeted components. Selective autophagy relies on cargo receptors that recognize targeted components and recruit them to autophagosomes through interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 102 publications
1
28
0
Order By: Relevance
“…Almost all autophagy-related receptors/adaptors identified to date have ATG8 interaction domains (AIMs/UIMs) or can directly interact with ATG8. These results imply sophisticated roles of ATG8 in autophagy and plant development or stress response, which were illustrated in detail in recent reviews [55][56][57].…”
Section: Comparison Of Plants and Yeast Core Autophagy Componentsmentioning
confidence: 60%
See 1 more Smart Citation
“…Almost all autophagy-related receptors/adaptors identified to date have ATG8 interaction domains (AIMs/UIMs) or can directly interact with ATG8. These results imply sophisticated roles of ATG8 in autophagy and plant development or stress response, which were illustrated in detail in recent reviews [55][56][57].…”
Section: Comparison Of Plants and Yeast Core Autophagy Componentsmentioning
confidence: 60%
“…Autophagy was initially defined as a bulk degradation process that causes massive degradation of cellular components; however, in recent years, cumulative evidence has indicated that the recruitment of cargo to autophagosomes is highly selective [56,93]. Several selective autophagy receptors have been characterized in plants.…”
Section: The Role Of Selected Autophagy In Plant Abiotic Stressmentioning
confidence: 99%
“…The selectivity of autophagy is achieved due to the involvement of selective autophagy cargo receptors. They recognize cargo and dock to the autophagosomes [ 129 , 130 ]. Autophagy, in contrast to the 26S proteasome, can not only degrade proteins and protein aggregates, but also entire organelles or their parts.…”
Section: Autophagy As a Cellular Degradation Pathway And A Part Of Intracellular Traffickingmentioning
confidence: 99%
“…There are three subtypes of autophagy depending on the mechanisms transporting the substrates in the lysosomes: macro-autophagy, micro-autophagy and chaperone-mediated autophagy (CMA). Macro-autophagy (the principal form of autophagy) is developed in response to stress and targets the release and degradation of every kind of aggregated protein and dysfunctional organelle by inducing a specific form of cytosolic vesicles, the autophagosomes[ 30 ]; the core machinery of autophagosome formation requires more than 40 largely conserved ATG[ 31 ]. Micro-autophagy, a non-selective procedure, is activated commonly to ingest senescent endoplasmic membranes by direct engulfment in the lysosome membrane[ 32 ]; it is the only constitutive autophagy mechanism that triggers small cytoplasmic debris engulfment into the lysosome for degradation[ 31 ].…”
Section: Autophagy: the Path And The Mapmentioning
confidence: 99%